Triple energy conversion cascade in a densely charged redox active covalent organic actuator - Bikash Garai; Gobinda Das; Connor M. Duncan; Hany F. Nour; Farah Benyettou; Thirumurugan Prakasam; Sabu Varghese; Houeida Issa Hamoud; Mohamad El-Roz; Jose Ignacio Martinez; Felipe Gándara; Mark A. Olson; et al. (Nature Communications)
Abstract Development of efficient actuators and understanding of their mechanisms are crucial for progress in areas such as soft robotics and artificial muscles. Here, we report a self-standing film of an ionic covalent organic framework (V 2+ –TG) composed of cationic guanidinium and viologen linkers, which shows an instantaneous and reversible photoactuation. Upon UV light exposure, the film deflects by 100 ° in less than 3 s, through a triple energy conversion cascade, where light is first converted into chemical energy via intramolecular charge transfer, then to thermal energy, and finally into mechanical energy, causing the film to bend. The localized heat induces water molecule elimination, creating a hydrogen bonding gradient between the two surfaces of the film, triggering the bending. Actuation property of the film is modulated by varying film thickness, light intensity, and humidity. The film also demonstrates practical potential for applications like lifting payloads, heating, and surface deicing where ice accumulation poses operational risks.